Tatabentuk bahasa Indonesia : kajian ke arah tatabahasa deskriptif - Muslich, Masnur, 1956- (Rawamangun, Jakarta : Bumi Aksara, 2008)
Morphology of Indonesian language.
Includes bibliographical references (p. 141-143).
Keywords: Indonesian Language -- Morphology